Creating miniature ecosystem to increase student learning outcomes through guided discovery learning - Fatikhatun Nikmatus Sholihah; Suci Prihatiningtyas (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
Basic ecology is the basic science that studies the interrelationships between living things and their environment. One of the content in this course is terrestrial ecosystems. The aim of learning this subject is students can carry out experiments (practicum) both in the laboratory or in the UNWAHA environment. This research aims to improve the cognitive learning outcomes of students by applying guide discovery learning in making miniature ecosystems. This research uses a pra experiment design. This research uses a one-group pretest-posttest design research design that is doing a pre-test before implementation and a post-test after implementation. To know the increase of student's cognitive learning outcomes through guide discovery learning, used N-gain test and paired sample t-test. The research instruments used are observation sheets and tests (pre-test and post-test). The results showed that the cognitive learning outcomes of students increased with an average grade of 64 to 84. N-Gain results show that two students of low category, 16 students of moderate category, and three students of high category students. Based on the results of the t-test obtained Sig < 0.05 is 0.00. Then it can be stated that there is a significant difference between the value of pre-test and post-test. In other words, there was an increase in student learning outcomes after the implementation of discovery learning guide learning. Based on the average class and t-test results, concluded that guided discovery learning can increase student's cognitive learning outcomes.